Inhibitory effect of Zingiberaceae essential oils against Conopomorpha cramerella (Snellen) Lepidoptera: Gracillariidae: Inhibitory effect of Zingiberaceae essential oils against C. cramerella (Journal of the Bangladesh Agricultural University, 2019)
Zingiberaceae (Order: Zingiberales) is recognized as the essential herbaceous species in the tropics. Several species of Zingiberaceae have shown potential in managing some Lepidopteran and Dipteran pests. Currently, there is no report in Malaysia explores the potential use of Zingiberaceae in managing cocoa pests, particularly the Cocoa pod borer (CPB), Conopomorpha cramerella. The study was conducted to evaluate the potential of Zingiberaceae as an adult emergence inhibition of C. cramerella using three locally grown species in Malaysia; Alpinia galanga (galanga), Curcuma longa (turmeric), and Zingiber officinale (ginger). Different ages of the CPB pupa (Days 1, 2, 3, 4, and 5) were selected and were sprayed with Zingiberaceae essential oils (EOs). Pupa was sprayed with EOs at four different concentrations; 100, 200, 400, and 800 ppm. Observations were carried out after 5 to 7 days, where the percentage of the unhatched pupa and healthy adult was recorded. The percentage of the deformed adults were examined based on the abdomen, the antenna, the wings, and overall deformities. The study was repeated four times for each EOs. Results denoted that the percentage of the unhatched pupa was the highest at C. longa (49.75 % a) and significantly different (p